Fertility desire and associated factors among women of reproductive age living with HIV/AIDS attending antiretroviral therapy clinic in Arba Minch General Hospital, South Ethiopia, 2021 - Tufa, Disasa; Wassihun, Biresaw; Misker, Direslgne; Beyene, Kassaw (Frontiers in Global Women's Health, 2023)
Background: The fertility desire of HIV-positive women to have children can have significant public health implications. Despite the increase in the number of HIV-positive women, the issues of fertility desire have not been studied in the study area. The study aimed to assess fertility desire and associated factors among women living with HIV/AIDS. Methods: a facility-based cross-sectional study was conducted from May 01 to July 30, 2021. A systematic sampling technique was used. The data were collected and entered into EpiData 3.1 and exported to the statical package for social science Version 25 for analysis. Binary logistic regression analyses were used to identify factors and a p-value of < 0.05 with a 95% confidence level was declared as statistically significant. Result: In this study (47.8%) of women had fertility desire. parents' pressure [AOR=4.41 ,95% CI (2.15, 9.05)], community pressure [AOR=2.62, 95% CI (1.30. 5.26)], being married [AOR=0.25,95%CI (0.09, 0.73)], have only girl/s [AOR=2.57,95% CI (1.12 ,5.90)], and children HIV seropositive [AOR=2.45 ,95%CI (1.23 ,4.85)] had statsticaly significant association. Conclusion: Fertility desire in the study area was high. Parents' pressure, community pressure, being married and having only girl/s, and children with HIV seropositive were factors that influence the fertility desire. Policymakers and health care providers who are working on an anti retroviral therapy(ART) clinic would like to try to consider the effects of these factors on women living with HIV while developing interventions on sexual and reproductive health issues. Strengthening prevention of mother to child transmition (PMTCT) service should consider the fertility desire of mothers living with HIV.